2019
DOI: 10.3390/met9060677
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Experimental Thermal Methods for the Fatigue Limit Evaluation of a Stainless Steel

Abstract: This paper regards the rapid determination of fatigue limit by using thermal data analysis. Different approaches available in the literature to estimate the fatigue limit of cold-drawn AISI 304L bars are analyzed and compared, namely, temperature- and energy-based methods. Among the temperature-based approaches, the Risitano Method (RM) and the method based on material temperature evolution recorded during a static tensile test were analyzed. Regarding the energy-based approaches, the input mechanical energy d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 37 publications
(104 reference statements)
0
42
0
Order By: Relevance
“…According to an experimental protocol, already adopted for other materials by Risitano et Al. [4,5], the Critical Stress  cL (load/area of the cross section) can be defined. The results of the research shown how the thermal analysis permits to identify the stress that produces the first local cracking in the specimen, with loads different and lower (50% -70%) from the breaking load Rck.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to an experimental protocol, already adopted for other materials by Risitano et Al. [4,5], the Critical Stress  cL (load/area of the cross section) can be defined. The results of the research shown how the thermal analysis permits to identify the stress that produces the first local cracking in the specimen, with loads different and lower (50% -70%) from the breaking load Rck.…”
Section: Discussionmentioning
confidence: 99%
“…In the last thirty years, many studies have shown that the temperature variation of a mechanical component under stress is a good parameter for estimate the energetic release, hence the residual fatigue life of the material [1][2][3]. Different papers showed as the thermal analysis applied to steel specimens [4][5][6], to composite specimens [7][8][9], to welding joints [10] permit to estimate the fatigue limit of the materials in easy and rapid way. Indeed, according to the thermo-elastic theory, under adiabatic conditions, there is a direct link between the applied stress and the temperature of the material.…”
Section: Introductionmentioning
confidence: 99%
“…A comparison among experimental methods for the fatigue limit evaluation of stainless steel has been presented in the work of Ricotta et al [2]. In particular, different approaches, temperature-based and energy-based, were used for evaluating the fatigue limit of cold-drawn AISI 304L bars.…”
Section: Contributionsmentioning
confidence: 99%
“…The advanced thermographic tools have put forward new methods for measuring energy generation and entropy production during fatigue tests 28 . Yang et al 29 used thermography for predicting high‐cycle fatigue of FV520B.…”
Section: Introductionmentioning
confidence: 99%